A revision and nomenclator of the Cainozoic mudwhelks (Mollusca: Caenogastropoda: Batillariidae, Potamididae) of the Paratethys Sea (Europe, Asia) - Harzhauser, Mathias; Guzhov, Aleksandr; Landau, Bernard (Zootaxa, 2023)
We present an in-depth revision of the Batillariidae and Potamididae from the Oligocene to the Pliocene of the Paratethys Sea, covering a geographic area of about 3 million km2 and a temporal frame of 23 Ma. A strong focus of this paper is laid on the consideration of rare and little known literature describing especially faunas from areas of the Eastern Paratethys Sea. The whereabouts of type material was evaluated and lectotypes are defined wherever necessary to clarify the status of most of the available names.In total, we traced 236 species-level names, which have been proposed for Paratethyan Batillariidae and Potamididae. After critical revision, only 28 of these names are accepted herein as valid species. This means that about 90% of the names found in the literature represent junior synonyms or misidentifications.Despite the tendency of several species to form convergent morphologies, the development of early teleoconch whorls allows a clear separation at the genus level. The Paratethyan Batillariidae and Potamididae are placed herein into 10 genera, of which Pustulosia nov. gen. (Batillariidae) and Theodisca nov. gen. (Potamididae) are introduced as new genera. Tiaracerithium Sacco, 1895 and Tiarapirenella Sacco, 1895 are reestablished as valid genera, which have been largely ignored or incorrectly applied in the literature. The second part of this paper comprises an annotated nomenclator of all species-level names used for Paratethyan mudwhelks. This nomenclator provides information on type material, type locality, stratigraphy and geographic distribution.